Acute Kidney Injury in Pediatric Diabetic Kidney Disease - Piani, Federica; Reinicke, Trenton; Borghi, Claudio; Tommerdahl, Kalie L.; Cara-Fuentes, Gabriel; Johnson, Richard J.; Bjornstad, Petter (Frontiers in Pediatrics, 2021)
Diabetic kidney disease (DKD) is a common complication of type 1 and 2 diabetes and often presents during adolescence and young adulthood. Given the growing incidence of both type 1 and type 2 diabetes in children and adolescents, DKD represents a significant public health problem. Acute kidney injury (AKI) in youth with diabetes is strongly associated with risk of DKD development. This review will summarize the epidemiology and pathophysiology of AKI in children with diabetes, the relationship between AKI and DKD, and the potential therapeutic interventions. Finally, we will appraise the impact of the recent COVID-19 infection pandemic on AKI in children with diabetes.